Spatial heterogeneity in nutrient utilization during the end-Devonian ocean anoxic event: a case study of the Western Canada sedimentary basin - Dhar, Sanjukta; Frucci, Mason N.; Atchley, Stacy C.; Fulton, James M. (Frontiers in Earth Science, 2024)
The Devonian-Carboniferous (D-C; 359 Ma) boundary is marked by widespread deposition of organic-matter-rich black shales associated with the Hangenberg mass extinction event. The Exshaw Formation spans the D-C boundary in the Western Canada Sedimentary Basin (WCSB) and includes the basal Exshaw Shale deposited under broadly anoxic waters. The sediments at the base of the Exshaw Shale were deposited synchronously during a transgressive event across the WCSB, spanning the geographic variability of the basin. The variable Corg content of the shale was affected by local nutrient upwelling and paleotectonic features impacting water depth and circulation. To characterize the link between paleogeography and nutrient cycling, geographic (N = 20 locations) and stratigraphic (N = 6 locations) trends of δ13Corg and δ15Nbulk were examined throughout the WCSB, representing a range of depositional settings. The δ15Nbulk values range between 0.0 and 6.3‰ and δ13Corg from −29.5 to −26.8‰. Phytoplankton production in focused upwelling zones acquired a relatively 15N-depleted signature through isotopic fractionation during nutrient assimilation, and the residual nutrient pool was 15N-enriched. The advection of surface waters away from the location of upwelling supported additional phytoplankton growth and the deposition of sediments with higher δ15N values. The stratigraphic sections include black laminated and burrowed mudrock sequences that record changes in paleoredox conditions, water depth, and tectonism over time. Up-core from the base of the Exshaw, the Corg content decreases and simultaneously δ15Nbulk increases, suggesting a decrease in eutrophic conditions. Variable δ13Corg and δ15Nbulk trends demonstrate that there is no “type” isotopic profile spanning the D-C boundary in the WCSB.